Ecology of Predation and Scavenging and the Interface - Moleón, Marcos (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Predation and scavenging are pervasive ecological interactions in both terrestrial and aquatic environments. The ecology, evolution and conservation of predators and scavengers have received wide scientific attention and public awareness. However, the close connection that exists between predation and scavenging has not been emphasized until very recently. The recognition that carnivorous animals may obtain meat by either hunting prey or scavenging their carcasses has profound implications from individual behavior to population, community and ecosystem levels. However, many relevant questions still remain unexplored. This book deals with some of these questions, with the final aim to definitively dismiss the traditional view that predation and scavenging are disconnected ecological processes. This compendium of science may help to inspire ecologists, evolutionary biologists, paleontologists, anthropologists, epidemiologists, forensic scientists, anatomists, and, of course, conservation biologists in their stimulating and promising endeavor of achieving a more comprehensive understanding of carnivory in a rapidly changing world.